126 Primary percutaneous coronary intervention for ST-elevation myocardial infarction in octogenarians. (22nd September 2015) - Jones, D A; Wicks, E; Gulati, A; Rathod, K; Guttmann, O; Jain, A; Knight, C; Rothman, M T; Mathur, A; Wragg, A
Abstract : Background: The western world consists of an ageing population. As a consequence, the number of Octogenarians (>80 s) undergoing primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) is increasing. Currently, little is known about their clinical characteristics or outcomes after primary PCI for STEMI. We therefore analysed such variables to establish an optimal treatment strategy for octogenarians. Methods: Clinical information was analysed from a prospective database of 1717 STEMI patients who underwent PCI between October 2004 and February 2009 at a London centre. Information was entered at the time of procedure and outcome assessed by all-cause mortality provided by the Office of National Statistics via the BCIS/CCAD national audit. The primary end point was major adverse cardiac events (MACE), defined as death, myocardial infarction (MI), stroke and target vessel revascularization (TVR). Results: A total of 267 Octogenarians (15.6% of the study population) with an average age of 82.5 years (range: 80–94), were treated with primary PCI. Of these, 51% (137/267) were male, 34% (88/259) had 3VD, 20% (54/267) had a previous history of MI, 17% (45/267) were diabetic and 12% (31/267) presented in cardiogenic shock. The Octogenarians had significantly greater co-morbidities than their younger counterparts (see Abstract 126 Table 1 ). Excluding those presenting in cardiogenic shock, 30-day and 1-year mortality rates within the octogenarian cohort were 4% and 10%, respectively. These were significantly higher than mortality rates within the younger subgroup (30-day 2%, 1-year 4% p<0.0001). After a 3-year follow up period, there was also a significantly higher MACE in the elderly group compared with the younger subgroup (p=0.0036) (Abstract 126 Figure 1 ). This was driven by all-cause mortality rather than by significant differences in rates of MI, stroke or TVR. Conclusion: Octogenarians constitute an increasingly important subgroup of STEMI patients and mortality amongst them is higher than younger counterparts. Little is known about their optimal treatment as they are underrepresented in randomised clinical trials, however the mortality figures in those patients not presenting in cardiogenic shock is encouraging.